THYROID FUNCTION IN DOGS WITH VISCERAL LEISHMANIASIS - Cardoso, Mauro Jose Lahm; Melussi, Maira; Fagnani, Rafael; Holsback, Luciane; Patelli, Thais Helena; Oba, Eunice (Universidade Federal de Goiás, 2016)
Abstract Several non-thyroid factors such as age, breed, concomitant diseases and use of certain drugs might influence the diagnosis of hypothyroidism in dogs. Changes in the concentrations of thyroid hormones due to non-thyroid illnesses are named euthyroid sick syndrome. The aim of this study was to evaluate the influence of visceral leishmaniasis on thyroid function in dogs without clinical signs of hypothyroidism, with or without azotemia. Positive animals for leishmaniasis were divided into six groups (absence or presence of hypoalbuminemia, normal or increased creatinine, normal or increased urea). The effect on these groups was evaluated on the thyroid-stimulating hormone (TSH), total thyroxine (TT4) and free thyroxine (FT4) concentrations. Dogs that were positive for leishmaniasis, by ELISA test, presented thyroid-stimulating hormone serum concentrations greater than seronegative animals, while total thyroxine and free thyroxine in dogs with leishmanisis were lower (P≤0.01) when compared to healthy dogs. However, the results were within the values for euthyroid animals. In seropositive dogs for leishmaniasis, TT4 showed statistically significant difference (P≤0.04) in the group with hypoalbuminemia compared to the group with normoalbuminemia, respectively, 1,01ug/dL and 1.4 g/dL. Based on this study, we could conclude that positive dogs for visceral leishmaniasis have not presented euthyroid sick syndrome, although when compared to healthy dogs, FT4 and TT4 were reduced and TSH increased.

Resumo Vários fatores extratireoidianos como idade, raça, doenças concomitantes e fármacos podem influenciar na função e no diagnóstico do hipotireoidismo em cães. As alterações nas concentrações dos hormônios tireoidianos decorrentes de doenças não tireoidianas é denominada de síndrome do eutireoideo doente. O objetivo deste estudo foi avaliar a influência da leishmaniose visceral na função da tireoide em cães sem sinais de hipotireoidismo, com ou sem azotemia. Os animais positivos para leishmaniose foram divididos em seis grupos (albumina nornal ou diminuída, creatinina normal ou elevada, uréia normal ou elevada) e foi avaliado o efeito nesses grupos das concentrações séricas do hormônio estimulante da tireoide (TSH), tiroxina total (TT4) e da tiroxina livre (FT4). Os cães positivos para leishmaniose, pelo teste de ELISA, apresentaram concentrações séricas de TSH mais elevadas do que os animais soronegativos, enquanto que as concentrações de TT4 e FT4 em cães com leishmaniose foram menores (P <0,01) quando comparadas com as dos cães saudáveis. No entanto, os resultados estavam no intervalo dos valores para os animais eutireoideos. Nos cães seropositivos para leishmaniose, a TT4 apresentou diferença estatística significativa (P <0,04) no grupo com hipoalbuminemia em relação ao grupo com normoalbuminemia, respectivamente, 1,01ug/dL e 1,4ug/dL. Concluiu-se que os cães positivos para a leishmaniose visceral não desenvolveram síndrome do doente eutireóide, embora as concentrações de TT4 e a FT4 estivessem reduzida e de TSH elevada em relação aos cães sem leishmaniose.
FUNÇÃO TIREOIDIANA DE CÃES COM LEISHMANIOSE VISCERAL
Keywords: euthyroid; hypothyroidism; leishmania; sick syndrome; thyroxine; eutiroidismo; hipotireoidismo; leishmania; síndrome do doente eutireoideo; tiroxina